Pelatihan Tadarus Al-Qur’an dengan Metode 5T Bagi Musyrif Ponpes Baitul Qur’an Subang - Ela Sartika; Khoirul Muhtadin; Amin Amin; Abdul Rohman; Wahyudi Wahyudi (Universitas Darunnajah, Jakarta, Indonesia, 2025)
The Quran recitation training using the 5T method for supervisors at the Baitul Quran Islamic Boarding School was motivated by the main issue of the low variety of methods used by students to understand Quranic verses, considering the challenges of the digital era that demand religious guidance based on structured, adaptive, and relevant methods. The objective of this activity is to equip supervisors with the skills to apply the 5T method (Tamhid, Tilawah, Tafsir, Tadabbur, and Tazkiyah) so that they can enhance the quality of students' Quran recitation in a more systematic and comprehensive manner. The research methodology was conducted in three stages: planning, implementation, and evaluation. The training results showed that musyrif experienced an improvement in their skills in understanding and practicing Quran recitation using the 5T method. Additionally, participants were able to integrate the aspects of recitation with the application of the meanings of Quranic verses, although further follow-up in the form of continued mentoring and the utilization of digital media is still needed to optimize the implementation of the 5T method.